Design and Evaluation of Learning Management System Framework to Foster Self-Regulated Learning Through Islamic Analogical Thinking in Physics - Rufaida, Salwa; Ishaq, Ishaq; Putria Dewi Sari, Melani (Electronic Journal of Education, Social Economics and Technology, 2025)
Student-centered learning systems according to their individual needs and learning styles are rarely found in physics learning. This study aims to present the design and validation of a learning system development that collaborates self-regulated learning with Islamic analogical thinking that is packaged in a Learning Management System platform so that physics learning is more meaningful. This study uses a quantitative descriptive approach to describe the validity of the self-regulated learning model based on Islamic analogical thinking in the learning management system. Data were obtained through questionnaires and expert validation sheets and then analyzed descriptively to assess the feasibility of the content, construction, and integration of Islamic values. Based on expert validation, a CVI score of 0.93 was obtained based on the format and learning instruction aspects, a CVI score of 0.89 based on the content and content aspects of learning materials, a CVI score of 0.94 based on the flexibility and adaptability aspects, and a CVI score of 0.92 based on the grammar aspect of learning presentation from a maximum CVI score of 1.00. The findings indicate that the self-regulated learning system based on Islamic Analogical Thinking is valid for application in the physics learning process.